Web ontology language - Business Process Customization Based Dynamic Customization for Composite Web Service (International Journal of Scientific Research and Management (IJSRM), 2014)
We propose to develop a trust system based on processing the payment reports to maintain a trust value for each node. The nodes that relay message more successfully will have higher trust values, such as the low-mobility and the large-hardware-resources nodes. Based on these trust value, we will propose a trust-based routing protocol to route message through the highly trusted node (which performance packet relay more successfully in the past) to minimize the probability of dropping the messages, and thus improve the network performance in terms of throughput and packet delivery ratio. The nodes submit lightweight payment report to the AC to update their credit accounts, and temporarily store undeniable security token called Evidences. The reports contain the alleged charges and rewards of different sessions with security proofs. The A C verifies the payment by investigating the consistency of the reports, and clears the payment of the fair reports with almost number of cryptographic operation. For cheating reports, the evidences are requested to identify and evict the cheating nodes , that submit correct reports. Evidence aggregation technique is used to increase the storage area of the Evidences. Evidences are submitted and the AC applies cryptographic operations to verify them only in case of cheating, but the nodes always submit security tokens. However, the trust system should be secure against singular and collusive attacks, and the routing protocol should make smart decisions regarding node selection with low overhead.